Collaborative United Kingdom-Australasian study of cancer in patients treated with immunosuppressive drugs. - Kinlen, L; Sheil, A; Peto, J; Doll, R (1979)
A collaborative study including centres in the United Kingdom, Australia, and New Zealand was instituted in 1970 to determine the incidence of cancer in patients treated for at least three months with azathioprine, cyclophosphamide, or chlorambucil. Follow-up of 3823 renal transplant recipients showed an almost 60-fold increase of non-Hodgkin's lymphoma together with an excess of squamous-cell skin cancer and mesenchymal tumours. A series of 1349 patients without transplants showed an excess of the same tumours, though to a less extent. These preliminary findings provide no clear evidence that immunosuppressive drugs produce the increased risk of most of the common cancers that might be expected from the simplest interpretation of impaired "immunosurveillance."